Modification of Diamond Surface by Femtosecond Laser Pulses - Vitali V. Kononenko (Photonics, 2023)
The basic mechanisms of laser interaction with synthetic diamond are reviewed. The characteristics of the main regimes of diamond surface etching are considered. In addition to the well-known graphitization and ablation processes, nanoablation and accumulative graphitization, which have attracted relatively recent attention, are described in detail. The focus is on femtosecond (fs) laser exposure, which allows for the formation of a dense cold electron–hole plasma in the focal zone and minimal overheating in the surrounding area. This potentially opens the way to the development of unique laser-based technologies that combine physical and chemical processes for precise surface treatment and functionalization. The physical limitations that determine how precisely the diamond surface can be treated by short-pulsed laser radiation and possible ways to overcome them with the ultimate goal of removing ultrathin layers of the material are discussed. Special attention is paid to the novel possibility of inducing the local formation of point active defects—nitrogen vacancy (NV) complexes in the laser-irradiated zone. Such defects have been at the forefront of solid-state physics for the past thirty years due to continuous attempts to exploit their unique properties in quantum optics, quantum computing, magnetometry, probing, and other fields. Both regimes of NV center formation with and without graphitization of the diamond lattice are considered. Thus, it is shown that intense pulsed laser irradiation is a perfect tool for the processing of synthetic diamonds at the micro-, nano-, and even at the atomic level, which can be well controlled and managed.